2018
DOI: 10.1055/s-0044-102130
|View full text |Cite
|
Sign up to set email alerts
|

Does Chronic Ankle Instability Influence Knee Biomechanics of Females during Inverted Surface Landings?

Abstract: The primary purpose of the study was to determine whether atypical knee biomechanics are exhibited during landing on an inverted surface. A seven-camera motion analysis system and two force plates were used to collect lower extremity biomechanics from two groups of female participants: 21 subjects with chronic ankle instability (CAI) and 21 with pair-matched controls. Subjects performed ten landings onto inverted and flat platforms on the CAI/matched and non-test limbs, respectively. Knee and ankle joint angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…No group-difference in peak values was found, which could indicate that the CAI group likely experienced similar peak ACL loadings versus controls. Previous studies [5,6] have observed greater knee extension and internal rotation moment, greater rectus femoris activation, but less biceps femoris activation, and suggest these altered knee biomechanics and muscle activations of CAI could relate to the increased ACL loading. However, this may not be true based on our tibiofemoral contact force data.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…No group-difference in peak values was found, which could indicate that the CAI group likely experienced similar peak ACL loadings versus controls. Previous studies [5,6] have observed greater knee extension and internal rotation moment, greater rectus femoris activation, but less biceps femoris activation, and suggest these altered knee biomechanics and muscle activations of CAI could relate to the increased ACL loading. However, this may not be true based on our tibiofemoral contact force data.…”
Section: Discussionmentioning
confidence: 80%
“…However, this may not be true based on our tibiofemoral contact force data. The possible reason was that the CAI group also exhibited a greater knee flexion angle [5] that could decrease the tibial anterior shear force by decreasing the patella tendon-tibia shaft angle [9,10]. Therefore, it is still unclear whether CAI could increase the ACL loading during landings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-two individuals with CAI and thirty-one healthy controls (matched according to age, sex and body mass index) were recruited among students and staff of the XXXX in XXXX, but also through the university's outpatient podiatry clinic and advertisement on social media. The sample size was determined a-priori from two previous studies that assessed jump landing kinematics and EMG on an inclined surface 15,16 with G-Power software (Version 3.1, Kiel, Germany). It was determined that for ankle inversion, peroneus longus preactivation and knee flexion, a total of 38 to 58 participants was necessary to obtain alpha, beta and Cohen's d effect size of respectively 0.05, 0.2 and 0.75 to 0.94.…”
Section: Methodsmentioning
confidence: 99%
“…During landing on more challenging surfaces such as unstable 13 or inclined, [13][14][15] altered lower limb biomechanics could place individuals with CAI at greater risk of sustaining recurrent LAS. Indeed, previous studies that quantified lower limb biomechanics during unilateral drop jump landing on an inclined surface (WEDGE) showed a longer peroneus longus activation latency, 14,15 reduced peroneus longus activation, 13,15,16 reduced gluteus medius muscle activation 13 and greater ankle inversion angles 14,15,17 in individuals with CAI compared to healthy counterparts. During unilateral drop jump landing on an unstable surface (FOAM), greater ankle dorsiflexion angles were reported between participants with CAI and healthy controls.…”
Section: O N L I N E F I R S Tmentioning
confidence: 96%